Cybersecurity legal frameworks in Vietnam and Japan: A Comparative Analysis - Vũ, Phương Linh (2020)
This research purpose is to find out the differences between cybersecurity legal frameworks in Japan and Vietnam and the reasons why they happen. From that point, the author will find out the effects which caused by these two legal structures and analyze what is the strong points and weaknesses from both flameworks, and how to improve both of them.